Research on frequency control of micro-grid - Li, Han Chao (2016)
For the past few years, micro-grid obtained rapid expansion with the growing concern on renewable energy, efficiency and reliable power supply and economic savings. It plays an important role in harmonize the contradiction between distributed generation (DG) and main grid. But when active power vacancy happened, strong fluctuation will be triggered due to the own features of micro-grid. This fluctuation may affect the system’s reliability and power quality.